An evaluation methodology for measuring the long-term impact of family strengthening and alternative child care services: the case of SOS Children’s Villages - Willi, Rosalind; Reed, Douglas; Houedenou, Germain (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2020)
Until recently, SOS Children’s Villages International, like many organisations in the social sector, lacked a rigorous and systematic approach to gauging the long-term impact of their services. With this in mind, SOS Children’s Villages International developed a social impact evaluation methodology in 2014 to measure the long-term effects of its services on children and their families and communities, as well as the social return on investment. This evaluation methodology has been tested and applied to similar service types across 15 low-, middle-, and high-income countries worldwide. The findings are regularly consolidated, in order to derive trends and learnings for the global organisation and to inform strategy and policy. The present article will discuss the evaluation methodology and the related limitations. Conclusions regarding the validity of the methodology will be offered in terms of the measurement of social service impact and the way forward.